THE ANTAGONISM BETWEEN THYROID AND PARATHYROID GLANDS - Uhlenhuth, Eduard (The Rockefeller University Press, 1918)
From the facts stated in this paper it is evident that the thymus gland of mammals contains a substance which is capable of producing tetany when fed to the larvæ of certain species of salamanders (Ambystoma opacum and Ambystoma maculatum). As long as the larvæ have not developed their own thymus glands, they are able, by means of some mechanism, to counterbalance the tetanic action of the thymus substance introduced in their food. When, however, the secretion from their own thymus glands is added to the thymus material introduced with the food, this mechanism of preventing tetany becomes inadequate and tetany ensues. In the larva of a third species of salamander, Ambystoma tigrinum, this mechanism will prevent tetany even when the larvæ are fed on thymus. In mammals the parathyroids are known to prevent tetany and are supposed either to absorb the tetany-producing substance and thus prevent its action or to change it into another non-toxic substance. It is at least probable that in the amphibians the parathyroids play the same rôle. Larvæ of anuran amphibians, which develop their parathyroids soon after hatching, never show tetanic convulsions if they are fed on thymus, but in certain species of salamanders, whose parathyroids develop only during metamorphosis, the larvæ invariably have tetanic convulsions upon thymus feeding, while the metamorphosed animals never show tetany. But in addition to the parathyroids the salamanders must possess still another mechanism which during the larval period inhibits the production of tetany by the animal's own thymus glands. In the larvæ of Ambystoma opacum and Ambystoma maculatum this mechanism is sufficient only to prevent tetany from the animal's own thymus, while in the larvæ of Ambystoma tigrinum it is capable of preventing tetany even when the larvæ are fed with thymus. If the thymus is the organ by whose action tetany is produced, we can understand why tetany in human beings occurs far more frequently in children than in adults, since in the latter the thymus gland is replaced, at least to a great extent, by connective tissue. The relation of thymus to tetany may also possibly explain the occurrence of tetany during pregnancy; while the parathyroids of the mother may be sufficient to prevent tetany from her largely atrophied thymus, they may not be sufficient to prevent tetany from the excess of thymus substance furnished by the fetus to the blood of the mother.